2018
DOI: 10.5812/ijp.65742
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hypernatremic Dehydration and Thrombocytopenia: Its Prevalence and Relationship with Prognosis

Abstract: Background: Understanding the risk factors for neonatal hypernatremic dehydration (NHD) may help to control the problem of these infants. Objectives: In this study, the level of platelets in NHD infants and its relationship with prognosis have been evaluated. Methods: This study consisted of 390 neonates who were referred to the Neonatal Clinic, Emergency Ward and Neonatal Intensive Care Unit in Ghaem Hospital, Mashhad, Iran from 2011 -2017. Demographic data, symptoms of disease, physical examination, and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In fact, more complications and poor prognosis were seen in patients with thrombocytopenia. 27 The cause of decreased platelet count among infants is unknown in our study. Nonetheless, dehydration, hypernatremia, and azotemia in these infants may have inhibitory effects on the bone marrow or may cause a state with excessive peripheral platelet consumption.…”
Section: Resultsmentioning
confidence: 66%
“…In fact, more complications and poor prognosis were seen in patients with thrombocytopenia. 27 The cause of decreased platelet count among infants is unknown in our study. Nonetheless, dehydration, hypernatremia, and azotemia in these infants may have inhibitory effects on the bone marrow or may cause a state with excessive peripheral platelet consumption.…”
Section: Resultsmentioning
confidence: 66%
“…This was found to be significantly associated with the severity of hypernatremic dehydration, with thrombocytopenia being more severe in patients with severe hypernatremic dehydration. In a recent study by Boskabadi H et al, 21 thrombocytopenia was observed in 41% of patients with hypernatremia and 6% of isonatremic infants ( P < 0.05). Urea, creatinine, and blood glucose were higher in patients with hypernatremic dehydration with thrombocytopenia as compared with those with normal platelet count and hypernatremia.…”
Section: Discussionmentioning
confidence: 85%
“…However, there was no correlation between thrombocyte levels and serum Na levels. On the other hand, Boskabadi et al (34) have demonstrated a strong correlation between hypernatremia and thrombocytopenia and a poorer prognosis and significantly more complications in thrombocytopenia patients. Babies born early term were found to have significantly lower serum sodium and glucose levels, higher antimicrobial usage rates, and a higher frequency of mixed feeding.…”
Section: Discussionmentioning
confidence: 98%